Molecular dissection of an immunodominant epitope in Kv1.2-exclusive autoimmunity - Talucci, Ivan; Arlt, Friederike A.; Kreissner, Kai O.; Nasouti, Mahoor; Wiessler, Anna-Lena; Miske, Ramona; Mindorf, Swantje; Dettmann, Inga; Moniri, Mehrnaz; Bayer, Markus; Broegger Christensen, Peter; Ayzenberg, Ilya; et al. (Frontiers in Immunology, 2024)
Subgroups of autoantibodies directed against Voltage-gated potassium channel (Kv) complex components have been associated with immunotherapy responsive clinical syndromes. The high prevalence and role of autoantibodies directly binding Kv remains, however, controversial. Our objective was to determine Kv autoantibody binding requirements and to clarify their contribution to the observed immune response. Binding epitopes were studied in sera (n=36) and cerebrospinal fluid (CSF) (n=12) from a patient cohort positive for Kv1.2, but negative for 32 common neurological autoantigens and controls (sera n=18; CSF n=5) by phospho and deep mutational scans. Autoantibody specificity and contribution to the observed immune response was resolved on recombinant cells cerebellum slices as well as nerve fibers. 83% of the patients (30/36) within the studied cohort shared one out of two major binding epitopes with Kv1.2-3 reactivity. 11% (4/36) sera showed no binding. Fingerprinting resolved close to identical sequence requirements for both shared epitopes. Kv autoantibody response is directed against juxtaparanodal regions in peripheral nerves and the axon initial segment in central nervous system neurons and exclusively mediated by the shared epitopes. Systematic mapping revealed two shared autoimmune responses, with one dominant Kv1.2-3 autoantibody epitope being unexpectedly prevalent. The conservation of the molecular binding requirements among these patients indicates a uniform autoantibody repertoire with monospecific reactivity. The enhanced sensitivity of the epitope-based (10/12) compared to the cell-based detection (CBA) (7/12) highlights its use for detection. The determined immunodominant epitope is also the primary immune response visible in tissue, suggesting diagnostic significance and specific value for routine screening.